Question
upstudy study bank question image url

When solving \( \boldsymbol{x} \) in the equation \( \boldsymbol{x}:-2 x^{2}+2 \geq-3 x \), the answer is \( \left\{x \left\lvert\,-\frac{1}{2} \leq x \geq 2\right.\right\} \) Select one: True False Solve the following inequality: \( x^{2} \geq-x+6 \) a. \( \{x \mid x \geq-3 \) or \( x \leq 2\} \) b. \( \{x \mid-3>x<2\} \) c. \( \{x \mid-3 \leq x \leq 2\} \) d. \( \{x \mid x \leq-3 \) or \( x \geq 2\} \) \( 12-2 x^{2}-y \leq 0 \) is a quadratic inequality. Select one:

Ask by Best Frank. in South Africa
Feb 18,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The first statement is **False**. The correct solution for the second inequality is option **d**: \( \{x \mid x \leq -3 \text{ or } x \geq 2\} \). The quadratic inequality \(12 - 2x^2 - y \leq 0\) is indeed a quadratic inequality.

Solution

Let's break down the problem step by step. ### Part 1: Analyzing the first inequality The inequality given is: \[ -2x^2 + 2 \geq -3x \] First, we can rearrange this inequality to standard form: \[ -2x^2 + 3x + 2 \geq 0 \] Next, we can multiply through by -1 (remembering to reverse the inequality): \[ 2x^2 - 3x - 2 \leq 0 \] Now, we will solve the quadratic equation \(2x^2 - 3x - 2 = 0\) to find the critical points. We can use the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] where \(a = 2\), \(b = -3\), and \(c = -2\). Calculating the discriminant: \[ b^2 - 4ac = (-3)^2 - 4(2)(-2) = 9 + 16 = 25 \] Now, substituting into the quadratic formula: \[ x = \frac{3 \pm \sqrt{25}}{2 \cdot 2} = \frac{3 \pm 5}{4} \] This gives us two solutions: \[ x_1 = \frac{8}{4} = 2, \quad x_2 = \frac{-2}{4} = -\frac{1}{2} \] Now we have the critical points \(x = -\frac{1}{2}\) and \(x = 2\). Next, we will test intervals around these critical points to determine where the inequality holds: 1. **Interval \( (-\infty, -\frac{1}{2}) \)**: Choose \(x = -1\): \[ 2(-1)^2 - 3(-1) - 2 = 2 + 3 - 2 = 3 \quad (\text{True}) \] 2. **Interval \( (-\frac{1}{2}, 2) \)**: Choose \(x = 0\): \[ 2(0)^2 - 3(0) - 2 = -2 \quad (\text{False}) \] 3. **Interval \( (2, \infty) \)**: Choose \(x = 3\): \[ 2(3)^2 - 3(3) - 2 = 18 - 9 - 2 = 7 \quad (\text{True}) \] Thus, the solution to the inequality \(2x^2 - 3x - 2 \leq 0\) is: \[ x \in \left[-\frac{1}{2}, 2\right] \] This means the statement \( \left\{x \mid -\frac{1}{2} \leq x \geq 2\right\} \) is **False**. ### Part 2: Solving the second inequality Now, we need to solve the inequality: \[ x^2 \geq -x + 6 \] Rearranging gives: \[ x^2 + x - 6 \geq 0 \] Next, we factor the quadratic: \[ (x + 3)(x - 2) \geq 0 \] The critical points are \(x = -3\) and \(x = 2\). We will test intervals around these points: 1. **Interval \( (-\infty, -3) \)**: Choose \(x = -4\): \[ (-4 + 3)(-4 - 2) = (-1)(-6) = 6 \quad (\text{True}) \] 2. **Interval \( (-3, 2) \)**: Choose \(x = 0\): \[ (0 + 3)(0 - 2) = (3)(-2) = -6 \quad (\text{False}) \] 3. **Interval \( (2, \infty) \)**: Choose \(x = 3\): \[ (3 + 3)(3 - 2) = (6)(1) = 6 \quad (\text{True}) \] Thus, the solution to the inequality \(x^2 + x - 6 \geq 0\) is: \[ x \in (-\infty, -3] \cup [2, \infty) \] This corresponds to option **d**: \( \{x \mid x \leq -3 \text{ or } x \geq 2\} \). ### Part 3: Analyzing the quadratic inequality The inequality \(12 - 2x^2 - y \leq 0\) can be rearranged to: \[ y \geq 12 - 2x^2 \] This represents a downward-opening parabola in the xy-plane. The statement that it is a quadratic inequality is **True**. ### Summary of Answers: 1. The first statement is **False**. 2. The correct option for the second inequality is **d**. 3. The statement about the quadratic inequality is **True**.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

Let’s break down that inequality! The given inequality \( x^{2} \geq -x + 6 \) can be rearranged to \( x^{2} + x - 6 \geq 0 \). Factoring gives us \( (x - 2)(x + 3) \geq 0 \). This tells us we need the product to be non-negative, which occurs in intervals \( (-\infty, -3] \) and \( [2, \infty) \). That matches option d, \( \{x \mid x \leq -3 \text{ or } x \geq 2\} \). So, the answer to your inequality is option d! Also, remember that when you see a quadratic inequality like \( 12 - 2x^{2} - y \leq 0 \), you can rearrange it into the standard form of a quadratic. Here, you'll find a downward-opening parabola due to the negative coefficient in front of \( x^2 \). Understanding the shape and vertex of the parabola can help you visualize solutions more clearly!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy